2006
DOI: 10.1136/bjsm.2005.024356
|View full text |Cite
|
Sign up to set email alerts
|

Single leg balance test to identify risk of ankle sprains

Abstract: Background: Ankle sprains are a common and potentially disabling injury. Successful prediction of susceptibility to ankle sprain injury with a simple test could allow ankle sprain prevention protocols to be initiated and help prevent disability in the athletic population. Objective: To investigate the ability of the single leg balance (SLB) test, carried out at preseason physical examination, to predict an ankle sprain during the autumn sports season. Design: Prospective cohort study Setting: High school varsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
7
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 20 publications
(14 reference statements)
4
127
7
7
Order By: Relevance
“…Other studies utilizing clinical assessments of postural stability have reported similar results, which underscores the likelihood of a neuromuscular predisposition for injury in certain athletes [33] . Muscle fatigue and loss of pre-injury strength may exacerbate neuromuscular impairment, resulting in the subsequent development of ankle instability [34] .…”
Section: Neuromuscular Controlsupporting
confidence: 63%
“…Other studies utilizing clinical assessments of postural stability have reported similar results, which underscores the likelihood of a neuromuscular predisposition for injury in certain athletes [33] . Muscle fatigue and loss of pre-injury strength may exacerbate neuromuscular impairment, resulting in the subsequent development of ankle instability [34] .…”
Section: Neuromuscular Controlsupporting
confidence: 63%
“…Neste sentido, a discussão dos resultados se torna difícil em relação a uma comparação direta com resultados da literatura. Entretanto, Trojian et al 17 20,21 , o que corrobora com os resultados do presente estudo nas correlações com o parâmetro A-COP. Este parâmetro identifica o deslocamento do COP em uma área correspondendo às direções anteroposterior e médio-lateral para manter o centro de massa do corpo dentro da base de sustentação 4 .…”
Section: Discussionunclassified
“…A narrower bimalleolar width is indicative of a smaller support base and reduced single-leg stability, which has been associated with increased ankle inversion injury occurrence (Trojian and McKeag, 2006). Royal Marine recruits regularly carry load during training activities (Beck et al, 1996;Blacker et al, 2008), thereby increasing the height of their centre of gravity, and reducing stability.…”
Section: Discussionmentioning
confidence: 99%